Analisis Dampak Faktor Internal, Pangsa Pasar, dan Strategi Pemasaran Terhadap Peningkatan Volume Penjualan PT. Indarla Sukses Abadi di Sukoharjo - Ayu Nur Septyaningrum, Listiana Diah; Susanti, Ari (STIE Atma Bhakti, 2025)
Internal factors, market share, and marketing strategies require further investigation. This study aims to analyze the impact of these factors on the increase in sales volume at PT. Indarla Sukses Abadi in Sukoharjo. A quantitative approach was applied with a sample of 50 respondents. The research instruments were tested using validity and reliability tests, and the results confirmed that all items were valid and reliable. Classical assumption tests indicated that the data were normally distributed, free from multicollinearity, and showed no signs of heteroscedasticity. Multiple linear regression analysis revealed that marketing strategy had a significant effect on sales volume, while internal factors and market share demonstrated a less significant influence on the dependent variable (Y). These findings suggest that improving internal factors and market share, while maintaining effective marketing strategies, are strategic steps to sustain and stabilize the sales volume of PT. Indarla Sukses Abadi.